Project MUSE (Johns Hopkins University Press, 1995)
Project MUSE is a leading provider of digital humanities and social science content for the scholarly community. Since 1995 the MUSE journal collections have supported a wide array of research needs at academic, public, special, and school libraries worldwide. MUSE is the trusted source of complete, full-text versions of scholarly journals from many of the world's leading university presses and scholarly societies, with over 120 publishers currently participating.
Gesehen am 06.08.03
Keywords: searchable full text; Datenbank; Books & Collections; A00 General